1995
DOI: 10.1073/pnas.92.22.10128
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/reductive conjugation of mannan to antigen selects for T1 or T2 immune responses.

Abstract: The induction of CD8+ cytotoxic T lymphocytes (CTLs) is desirable for immunization against many diseases, and recombinant-synthetic peptide antigens are now favored agents to use. However, a major problem is how to induce CTLs, which requires a Ti-type response to such synthetic antigens. We (refs. 4 and 5; unpublished data). The unusual finding is that if the conjugation is done under oxidizing conditions, then cell-mediated immunity is selectively stimulated, compared with using reducing conditions for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 28 publications
3
136
1
4
Order By: Relevance
“…The functionality of TLR4 in MDO presentation may also elucidate the adjuvant mechanism of oxidized mannan-conjugated fusion mucin 1 protein (MFP), of which the adjuvanticity is also TLR4-mediated (24,34). MFP has been used for immunotherapy in phase III cancer clinical trails (35).…”
Section: Discussionmentioning
confidence: 99%
“…The functionality of TLR4 in MDO presentation may also elucidate the adjuvant mechanism of oxidized mannan-conjugated fusion mucin 1 protein (MFP), of which the adjuvanticity is also TLR4-mediated (24,34). MFP has been used for immunotherapy in phase III cancer clinical trails (35).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive O-mannosylation of proteins greatly enhanced antigen delivery, and deglycosylation profoundly inhibited T cell responses [7]. The role of mannose residues in antigen delivery was also shown by the mannose polymer, mannan, which enhanced antigen-specific Th1/CTL and Th2/antibody responses in oxidized and reduced forms, respectively [9][10][11][12][13][14][15]. Oxidized mannan conjugated to recombinant MUC1 fusion protein has been used in Phase II/III cancer clinical trials [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that MR targeting can enhance the efficiency of MHC class II presentation to Ag-specific T cells by several orders of magnitude, relative to nontargeted Ag (17,18). In addition, conjugation of the human tumor Ag (mucin 1) to oxidized-mannan induced Th1 and CTL responses and complete tumor protection in mice (19,20). However, the overlapping pattern recognition of mannose-type ligands between MR and other CLRs, such as DC-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN), makes the interpretation of the MR contribution to the observed immune responses difficult (3,21).…”
mentioning
confidence: 99%